State estimation of energy saving on primary oil refining machines - Кривда, Вікторія Ігорівна (Technology audit and production reserves, 2015)
The generalized description of the primary oil refining process at the electric desalting machine is made. The basic shortcomings of modern domestic thermal power plants in the primary oil refining are shown. Identification of the main places and causes of inefficient use of primary energy resources helps identify energy saving potential in manufacturing. It is determined that the economic effect tends to increase in the event of changes in the structure of heat exchange equipment, especially through the use of compressors in a closed technological cycle of heat recovery. Using recuperative heat exchange at the facility of primary oil processing makes it possible to solve the feasibility problem of saving primary energy resources. Reducing pressure temperature value between hot and cold process lines of primary oil refining machine to 20 % causes an increase in economic benefits by nearly 10 %. Modernization of existing schemes of primary oil processing machines can increase a depth of processing and energy saving potential in manufacturing.